Increased number of live births by migrant mothers shows areal inequality in Japan: A descriptive study - Kimihiro Nishino; Souphalak Inthaphatha; Eiko Yamamoto (Elsevier, 2023)
Japan has not implemented policy of accepting many migrants, and the proportion of migrants in the total population is much smaller than that in other economically developed countries. Therefore, issues regarding the health status of migrants, especially migrant mothers and their children, have not been discussed enthusiastically in Japan. In the present study, we aimed to describe the epidemiology (time trend of the number, areal distribution, and frequency of maternal nationality of newborn births) of live births by migrant mothers in Japan, which contributes to the administration of medical policies on the perinatal care of migrant mothers. This study used data from the vital statistics reported by the Ministry of Health, Labour and Welfare (MHLW) of Japan and from foreign resident statistics reported by Immigration Services Agency (ISA) of Japan. To show areal inequality in the number of live births by migrant mothers, we applied the Gini coefficient. This study demonstrated that the number of live births by migrant mothers increased from 16,154 (1.31% of the total) in 1990 to 26,517 (3.08%) in 2020. It also showed stronger areal inequality at prefecture level by Japanese mothers (Gini coefficient; 0.64 vs 0.46 in 2020), and this areal inequality has increased during the last decade. This study also illustrated that the frequency of maternal nationality of newborns from migrant mothers has been altered in the last decade, especially in the composition of Asian countries. In conclusion, the number of live births by migrant mothers in Japan has been progressively increasing; however, this trend is excessively concentrated in specific areas in Japan. These tendencies are expected to become more prominent in the future, and their possible impacts on medical institutions and administrative agencies in specific areas that treat migrant mothers should be investigated and discussed.